2012
DOI: 10.1111/j.1365-2133.2012.11061.x
|View full text |Cite
|
Sign up to set email alerts
|

Overall treatment success after treatment of primary superficial basal cell carcinoma: a systematic review and meta-analysis of randomized and nonrandomized trials

Abstract: Pooled estimates from randomized and nonrandomized studies showed similar tumour-free survival at 1 year for imiquimod and PDT. The PDT tumour-free survival was higher in studies with repeated treatments. However, these results were largely derived from nonrandomized studies, and randomized studies with head-to-head comparison of imiquimod and PDT are lacking. There is a need for head-to-head comparison studies between PDT, imiquimod and other treatments with long-term follow-up to enable better recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
9

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 58 publications
(376 reference statements)
0
104
0
9
Order By: Relevance
“…Their Kaplan-Meir plot suggested a steeper slope for recurrences over years 1 to 3. Another systematic review of interventions for superficial BCC in 2012 found pooled estimates from 23 randomized and non-randomized studies of 87·3% for imiquimod (95% CI 84-91%) and 84·0% for PDT (95% CI 78-90%) (Roozeboom et al, 2012). A subsequently published non-inferiority RCT performed a head to head comparison between topical 5-FU, topical 5% imiquimod and methyl aminolevulinate-photodynamic therapy (MAL-PDT) in 601 patients with superficial BCC, followed up for 1 and 3 years (Arits et al, 2013;Roozeboom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Their Kaplan-Meir plot suggested a steeper slope for recurrences over years 1 to 3. Another systematic review of interventions for superficial BCC in 2012 found pooled estimates from 23 randomized and non-randomized studies of 87·3% for imiquimod (95% CI 84-91%) and 84·0% for PDT (95% CI 78-90%) (Roozeboom et al, 2012). A subsequently published non-inferiority RCT performed a head to head comparison between topical 5-FU, topical 5% imiquimod and methyl aminolevulinate-photodynamic therapy (MAL-PDT) in 601 patients with superficial BCC, followed up for 1 and 3 years (Arits et al, 2013;Roozeboom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[96][97][98] Monotherapy with topical 5-FU, an antimetabolite, for superficial BCC is less well studied in welldesigned RCTs. 74,75 Typical regimens include twice-daily application for 3 to 6 weeks. Adverse events are similar to those with imiquimod and include erythema, swelling, crust, erosions, ulcers, and eschar.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…35,38,64,74,76,77,[80][81][82]86,87,99 Application of the photosensitizer is often preceded by light curettage of BCCs. 99 Usually a single treatment cycle is performed, but treatments may be repeated.…”
Section: Photodynamic Therapymentioning
confidence: 99%
See 2 more Smart Citations